2022
DOI: 10.29407/intensif.v6i2.17509
|View full text |Cite
|
Sign up to set email alerts
|

Measuring The Success of E-Learning In Universities Using The Technology Acceptance Model

Abstract: This study aims to determine the factors of acceptance of e-learning technology in students who use the technology acceptance model, namely perceived usefulness (PU), perceived ease of use (PEOU), an attitude of acceptance of use (ATU), and acceptance (IT) of the e-learning acceptance system. The population in this study were students of state Islamic religious institutes who had participated in the e-learning system. The respondents of this study were students of the Ambon State Islamic Institute of Religion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Overall, this research adopts a quantitative approach, applies methods, and uses quantitative tools to be used concretely test research hypotheses [29]. The goal of this study is to determine Assumption of there is a relationship between application usability and user retention.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, this research adopts a quantitative approach, applies methods, and uses quantitative tools to be used concretely test research hypotheses [29]. The goal of this study is to determine Assumption of there is a relationship between application usability and user retention.…”
Section: Methodsmentioning
confidence: 99%
“…This surge in positive commentary is hypothesized based on TAM, suggesting that increased satisfaction with technological innovations leads to more favorable user feedback [11,31,50]. Studies have shown a tendency for improved perceptions as educational institutions iterate on their e-learning offerings [38,39].…”
Section: H4mentioning
confidence: 98%
“…Furthermore, research into student attitudes has revealed a complex landscape of acceptance and resistance, shaped by factors such as technological readiness, the quality of e-learning platforms, and the adequacy of support provided by educational institutions. Researchers studied the impact of COVID-19 on the teaching-learning process and aimed to discover students' attitudes to online instruction and their intention to use and their actual use of e-learning platforms in various countries around the globe: Cambodia [5], China [6,7], Egypt [8], Ethiopia [9], Germany [10], Indonesia [11], Iraq [12], Japan [13], Jor-dan [14][15][16][17][18], Kenya [19], Mauritius [20], Malaysia [21][22][23], Morocco [24], New Zealand [25], Palestine [26], Poland [2], Saudi Arabia [4,[27][28][29][30][31], South Africa [32], and Uganda [33].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Education is an industry that produces products and services based on scientific knowledge and skills [5]. One effort to achieve better education is to innovate [6], [7].…”
Section: Introductionmentioning
confidence: 99%